Developing Language Skills and Satisfaction Based on Task-Based Hierarchical Language Teaching Methods for Vocational Students at Chongzuo Early Childhood Teacher Education College Guangxi China - Qianhui, Liang; Bhothisarn , Phitorn (วารสารวิทยาลัยนครราชสีมา สาขามนุษยศาสตร์และสังคมศาสตร์, 2026)
The purposes of this research were to (1) compare students’ language skills before and after the implementation of Task-Based Hierarchical Language Teaching Methods. (2) examine students’ satisfaction toward Task-Based Hierarchical Language Teaching Methods on Language skills. The sample group used in this study is one class, 30 of Vocational Students at Chongzuo Early Childhood Teacher Education College Guangxi China students which was conducted by cluster random sampling. The research design was one-group pretest posttest design. The research instruments are included of (1) Task-Based Hierarchical Language Teaching Methods lesson plans which has the IOC The average of Content Validity is 0.94 (2) Language skills assessment test with The Average IOC = 0.91, the difficulty Index (P) Range: 0.42 – 0.78, Reliability coefficient = 0.89 3) Students’ satisfaction questionnaire of a five-point Likert scale, which was value of reliability was 0.86. The finding was as follow: (1) The post-test of language skills by using Task-Based Hierarchical Language Teaching Methods was higher than pretest with statistically significant at 0.05 level (2) The students’ satisfaction on language skills by using Task-Based Hierarchical Language Teaching Methods was at very high level in total ( = 4.55, S.D.=0.61)